2008
DOI: 10.1051/0004-6361:20079259
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 6 K gas in Ophiuchus D

Abstract: Context. Cold cores in interstellar molecular clouds represent the very first phase in star formation. The physical conditions of these objects are studied in order to understand how molecular clouds evolve and how stellar masses are determined. Aims. The purpose of this study is to probe conditions in the dense, starless clump Ophichus D (Oph D). Methods. The ground-state (1 10 → 1 11 ) rotational transition of ortho-H 2 D + was observed with APEX towards the density peak of Oph D.Results. The width of the H … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 29 publications
(56 reference statements)
7
78
1
Order By: Relevance
“…R CrA itself is a Herbig Be star (spectral class B5-B8; Gray et al 2006;Bibo et al 1992) with a mass of 3.0 M (Bibo et al 1992) and a luminosity between 100 and 166 L (the lower value is a lower limit from SED estimates with incomplete data in the UV range; Bibo et al 1992). Several dense molecular cloud cores with masses between 2 and 50 M were found near the Herbig Be star R CrA in C 18 O SEST observations by Harju et al (1993). The IRS7 region is located with its centre between the Herbig Be star R CrA and the T Tauri star T CrA (Taylor & Storey 1984), ∼30 (≈4000 AU) from each of these stars, and harbours a handful of Class 0/I YSOs.…”
Section: Introductionmentioning
confidence: 94%
“…R CrA itself is a Herbig Be star (spectral class B5-B8; Gray et al 2006;Bibo et al 1992) with a mass of 3.0 M (Bibo et al 1992) and a luminosity between 100 and 166 L (the lower value is a lower limit from SED estimates with incomplete data in the UV range; Bibo et al 1992). Several dense molecular cloud cores with masses between 2 and 50 M were found near the Herbig Be star R CrA in C 18 O SEST observations by Harju et al (1993). The IRS7 region is located with its centre between the Herbig Be star R CrA and the T Tauri star T CrA (Taylor & Storey 1984), ∼30 (≈4000 AU) from each of these stars, and harbours a handful of Class 0/I YSOs.…”
Section: Introductionmentioning
confidence: 94%
“…The real dust temperature inside the clumps cannot be directly measured and could be estimated only by modelling. From earlier theoretical studies, it is clear that in many cases the central temperature of the dense cores goes below 10 K (e.g., Evans et al 2001;Harju et al 2008). In particular, in LDN 183, our field G6.03+36.73, Pagani et al (2004) reported dust temperatures down to ∼7 K. In the dense and cold environment the dust grains are expected to undergo coagulation that can lead to increased opacity at submillimetre wavelengths (Ossenkopf 1993;Stepnik et al 2003;Ysard et al 2012;Köhler & et al 2012).…”
Section: Fig 11mentioning
confidence: 99%
“…10). The region has been studied by Harju et al (1993) in CO emission and with Spitzer by Peterson et al (2011), and it is reviewed in Neuhäuser & Forbrich (2008). The central object is the R Corona Australis dark cloud (R CrA), which has a tail extending to the bottom-left of the maps consisting of the reflection nebula NGC 6729.…”
Section: Diffuse Ame Regionsmentioning
confidence: 99%